MONTE CARLO SIMULATION IN PREDICTING THE SPREAD OF COVID-19 IN MEDAN CITY - Hasnah , Dara Nurul; Andriani , Dina; Sahpitri, Ely; Harahap, Zihan Rossus Aini (Pena Cendekia Insani, 2021)
Covid-19 or Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) is a new type of virus that has given up on the human respiratory system and is currently spreading throughout the world. So, this research will discuss the prediction of the spread of Covid-19 in Medan City. The method used is the Monte Carlo simulation. This method is used to determine the number of patients both ODP patients (people under observation), positive, recovered and died. The Monte Carlo simulation is carried out with the help of Microsoft Excel and the simulation is carried out with 1 to 1,000,000 repetitions. From the simulation results, the smallest error data is 0% and the largest error data is 6%.